KOMUNIKASI UNTUK PERUBAHAN SOSIAL BERBASIS PEMBERDAYAAN MASYARAKAT SIPIL DI PONDOK PESANTREN NURUL HAROMAIN - dkk, Anang Sujoko (UIN Mataram, 2018)
Islamic boarding schools become a great asset of the nation. Its existence has never subsided to continue to be explored as a source of great value. On the other hand the internal dynamics of the pesantren in responding to important times continue to be studied. This study aims to identify the problems and potential of Nurul Haromain Islamic Boarding School Malang Regency related to entrepreneurial management in managing the Q-Zulal water business. The design of Participation Action Research research is used as one of the qualitative methodologies. The results of this study indicate that the limitations of production management and human resources in managing the Q-Zulal water business as a basis for consideration in formulating planning and implementation of civil society-based empowerment programs. To overcome this problem, a group discussion, workshop and mentoring forum was conducted with a focus on production management and management resources. Through this activity, outputs are generated in the form of Standard Operating Procedures and structuring of management resources. Through this scheme, this research is not only a means of seeing the existing reality, but also as a part of communication for social change in empowering pesantren as agents of development